2013
DOI: 10.5862/mce.42.9
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of piles of various cross-sectional forms

Abstract: According to the authors the lack of evaluation methods for efficiency of pile behavior leads to an increased degree of randomness in the selection of type, material, shape and placement of piles, and, as a consequence, to overspending the material, energy, labor costs and, respectively, to more expensive construction. The work is devoted to the determination of the efficiency of piles of various cross-sectional forms (round, square, cross- shaped, T-shaped and double tee forms). A number of methods and crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Short piles are easy to install by using the effective drilling machines. The analysis of piles of various forms has shown that maximum efficiency was achieved under the minimum depth of 2 meters, and gradually decreased later (Bulatov and Kolosova, ).…”
Section: The Selection Of the Foundation For A Single‐storey Dwellingmentioning
confidence: 99%
“…Short piles are easy to install by using the effective drilling machines. The analysis of piles of various forms has shown that maximum efficiency was achieved under the minimum depth of 2 meters, and gradually decreased later (Bulatov and Kolosova, ).…”
Section: The Selection Of the Foundation For A Single‐storey Dwellingmentioning
confidence: 99%
“…Consequently, the question arises under the regulatory calculation method of bearing capacity of piles of reality and possibilities of its improvement. Some attempts to improve methods aimed at defining the analytical dependences existing regulations [28,29,30]. However the analysis shows that presented in these studies, depending modified variants of standard documents, therefore, no major changes to the existing methods are not followed and the end result of the analytical calculation of the bearing capacity of piles remained unchanged: in SP 24.13330 [25] for the calculation of the bearing capacity of a formula:…”
Section: Introductionmentioning
confidence: 99%
“…Another direction to minimize the differences of values of the calculated and actual bearing capacity of piles -improvement of construction technology [15,28,32]. But here, just changed the methodology of selection of equipment for piling and calculate its efficiency, which only indirectly affect the actual bearing capacity of piles.…”
Section: Introductionmentioning
confidence: 99%
“…By the method of construction piles can be monolithic -produced directly on construction sites, and prefabricated -produced on the factory. The superiority of prefabricated pile foundations particularly affects in soft soil conditions, where it is required to perform operations on dewatering for other types of foundations and even for monolithic pile foundations [2]. Moreover, it is more economy financially and in time saving because parts of such piles can be connected immediately, no need for well boring and to wait drying of construction as for monolithic one.…”
Section: Introductionmentioning
confidence: 99%